The Relationship Between Mental Health and Spiritual Intelligence Among Primary School Teachers - Karim Shateri; Ali Asghar Hayat; Hamdollah Jayervand (Shiraz University of Medical Sciences, 2019)
Background: Teaching is a highly stressful occupation and teachers suffer from more mental health problems than other professions. Objectives : The current research was aimed to investigate the relationship between spiritual intelligence and mental health among primary school teachers. Methods: A descriptive correlation design was applied in this study. The statistical population consisted of all teachers working in primary schools of Darreshahr in Ilam province during 2016 - 2017 academic year (N = 430), from whom 203 people were selected randomly as a sample, applying Cochran's sample size formula. Data were collected through spiritual intelligence self‐report inventory-24 (SISRI-24) and general health questionnaire (GHQ). The collected data were analyzed using Pearson correlation coefficient and regression analysis. Results: The results showed that the mean and standard deviation of mental health was 17.37 ± 9.32. In addition, findings indicated that the mean and standard deviation of spiritual intelligence and its components including critical existential thinking, personal meaning production, transcendental awareness, and conscious state expansion were 59.35 ± 12.88, 17.12 ± 4.22, 12.79 ± 3.50, 18.16 ± 4.98, and 11.26 ± 2.66, respectively. Furthermore, findings showed that there is a significant negative relationship between spiritual intelligence and mental health (- 0.43, P < 0.001). The results of the regression analysis showed that among the spiritual intelligence components, transcendental awareness (β = - 0.281, P < .001) and personal meaning production (β = - 0.244, P = 0.002) are better predictors for the teachers' mental health. Conclusions: According to the results of the present study, a higher level of spiritual intelligence leads to higher level of teachers' mental health. Therefore, it is recommended that education officials develop programs for training and enhancing teachers' spiritual intelligence that, in turn, can lead to the improvement of the teachers' mental health.